An in‐cell helicase reporter system for quantifying DDX3X and DDX3Y activities - Zhi Sheng Poh; James Chia Wei Tan; Brandon Han Siang Wong; Kottaiswamy Amuthavalli; Holy Kristanti; Suat Hoon Tan; Nicholas Francis Grigoropoulos; Navin Kumar Verma (Bioengineering & Translational Medicine)
Abstract Genome sequencing has identified numerous mutations in the DEAD‐box RNA helicases, DDX3X and DDX3Y, associated with cancer and other diseases, but monitoring of their functional consequences remains a challenge. Conventional helicase assays are laborious, often technically difficult, and are performed in cell‐free systems that do not address biologically relevant questions. Here, we developed an engineered DDX3 reporter cell system capable of interrogating helicase activities of DDX3X and DDX3Y and their mutational variants. For this, we deleted the endogenous DDX3X in human 293T cells using CRISPR/Cas9. DDX3Y is absent in 293T cells being a female‐derived line. We transfected cells with firefly luciferase plasmids that provided bioluminescence signals, depending on helicase activities of exogenously expressed wild‐type or mutant DDX3X or DDX3Y, and inserted Aequorea coerulescens Green Fluorescent Protein (AcGFP) as an internal control separated by an internal ribosome entry site (IRES). The developed reporter system can be applied to screen compound libraries targeting DDX3X or DDX3Y in living cells and study their functional roles in health and disease.